Beyond Innovation: Relational Capabilities as Drivers of Brand Equity and Customer Loyalty in Industrial SME Markets - Maria Wuri Handayani Handayani; Leonnard Ong (Journal of Sustainable Community Development (JSCD), 2026)
Marketing innovation is commonly regarded as a key driver of competitiveness; however, its effectiveness may vary across different market settings. In industrial SME ecosystems, where long-term collaboration and interdependence are central, relational capabilities may play a more decisive role than innovation-driven differentiation. This research focuses on how Strategic Marketing Innovation, Service Quality, and SME Empowerment influence Brand Equity and Customer Loyalty. Drawing on the Resource-Based View and Relationship Marketing Theory, it explores whether relational capabilities provide a stronger foundation for brand development than innovation-oriented strategies. Data were collected from 200 SME customers within the industrial flour supply chain in Java, Indonesia, and analyzed using PLS-SEM. The results show that Strategic Marketing Innovation does not significantly affect Brand Equity, whereas SME Empowerment and Service Quality have significant positive effects. Brand Equity, in turn, strongly influences Customer Loyalty. These results imply that relational qualities, rather than just innovation intensity, are more important in determining brand success and customer loyalty in partnership-oriented industrial marketplaces. They also emphasize how crucial relational techniques are to bolstering community-based industrial ecosystems and SME sustainability.